Teaching attitudes among Arabic language teachers of Arabic for non-native speakers in The Sultanate of Oman - Al-Isaee, Amer Salim Hamad; Al-Azri, Saif Nasser Saif (Journal of Educational and Psychological Sciences, 2023)
This study aimed to determine the teaching attitudes among Arabic language teachers of Arabic for non-native speakers in the Sultanate of Oman, in addition to uncover the impact of: gender and experience. The population consisted of (39) teachers were selected randomly, to achieve the goals of the study descriptive approach was used, and a questionnaire consisting of 40 items was used to collect data, and the result revealed that the total score of the instrument ranged from very high to high, it reached a very high degree in the integrative, communicative, and skillful dimensions, and a high degree in the functional dimintions, There are no statistically significant differences at the level of 0.05 among the study sample due to the gender variable in the functional and communicative directions, while the results showed that there are statistically significant differences at the level of 0.05 in the complementary and skillful directions in favor of female.
Keywords: teaching attitudes; Arabic for non speakers; sultanate of Oman